The Effect of Deoxynivalenol on Selected Populations of Immunocompetent Cells in Porcine Blood—A Preliminary Study - Michał Dąbrowski; Ewa Jakimiuk; Mirosław Baranowski; Magdalena Gajęcka; Łukasz Zielonka; Maciej Tadeusz Gajęcki (Molecules, 2017)
Deoxynivalenol (DON) is one of the most prevalent mycotoxins in Europe. Pigs are an animal species that is most susceptible to this mycotoxin. Deoxynivalenol causes significant losses in pig production by lowering feed intake, decreasing daily weight gains, disrupting immune responses, and increasing susceptibility to diseases. The aim of this experiment was to determine the influence of feed contaminated with DON at concentrations insignificantly higher than recommended by the European Commission (900 µg/kg). The experimental feed contained 1008 μg DON/kg. The experiment was performed on eight weaners from the same litter. The animals were randomly divided into two groups: an experimental group (M, n = 4) fed contaminated feed and a control group (C, n = 4) administered feed free of mycotoxins. The experiment lasted for six weeks, and peripheral blood samples were collected from the animals for analyses of selected morphological parameters and changes in the percentages of CD4+8−, CD4−8+, and CD4+8+ lymphocytes and antigen-presenting cells (APC) with CD14+172+ (monocytes), CD172ahigh4−14− (conventional dendritic cells, cDC), and CD172adim4+14− (plasmacytoid dendritic cells, pDC) phenotypes. The morphological parameters of porcine blood samples were determined by flow cytometry with non-fluorescent particle-size calibration standards, and no differences were observed between groups M and C. An immunophenotyping analysis of lymphocytes and dendritic cells (DC) revealed an increase in the percentage of CD4+8−, CD172ahigh4−14−, and CD172adim4+14− cells, and a decrease in the number of CD4−8+ cells in group M. The results of this experiment suggest that prolonged exposure to low doses of DON can change the proportions of immunocompetent cells (a shift towards humoral immunity), without affecting their overall counts.